1998
DOI: 10.1002/(sici)1097-0215(19980130)75:3<371::aid-ijc8>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Inducible protein in rat hepatomas with expression alternative to alpha‐fetoprotein

Abstract: The rat hepatoma cell line McA RH7777 was cloned into alpha‐fetoprotein‐producing (AFP+) and non‐producing (AFP−) sublines. A monoclonal antibody (MAb A2/3) reacting with an antigen (Ag A2/3) present only in AFP− clones or AFP− cells in mixed clones was obtained. Ag A2/3 was absent from the liver of embryonic, fetal, newborn and adult rats, but it was present in gastric and intestinal mucosa of adult rats. Ag A2/3 was found to be a heavy metal‐inducible protein: Cd2+ and Pb2+ strongly induced the expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…To investigate the antitumoral efficacy of the hybrid vector carrying mIL-12, orthotopic hepatocellular carcinomas were established in Buffalo rats by implantation of rat McA-RH7777 cells into the liver. This model was chosen because McA-RH7777 cells have been reported to express AFP (28). Our data showed that animals receiving HC-Ad-AFP-mIL-12 had a reduced tumor size (Fig.…”
Section: Resultsmentioning
confidence: 76%
“…To investigate the antitumoral efficacy of the hybrid vector carrying mIL-12, orthotopic hepatocellular carcinomas were established in Buffalo rats by implantation of rat McA-RH7777 cells into the liver. This model was chosen because McA-RH7777 cells have been reported to express AFP (28). Our data showed that animals receiving HC-Ad-AFP-mIL-12 had a reduced tumor size (Fig.…”
Section: Resultsmentioning
confidence: 76%